Climatic Analogues for the Administrative Districts of Nepal - Jha, Sasinath; Karn, Archana (Tribhuvan University Journal, 2011)
Available with Full text. Key words: Climatic Analogues; Scheme of thornthwaite; Evapotranspiration Tribhuvan University Journal Vol XXIII, No. 1, 2001 Page: 55-64 Uploaded date: 21 April, 2011